194X : architecture, planning, and consumer culture on the American home front - Shanken, Andrew Michael, 1968- (Architecture, landscape, and American culture series., 2009)
During the Second World War, American architecture was in a state of crisis. The rationing of building materials and restrictions on nonmilitary construction continued the privations that the profession had endured during the Great Depression. At the same time, the dramatic events of the 1930s and 1940s led many architects to believe that their profession--and society itself--would undergo a profound shift once the war ended, with private commissions giving way to centrally planned projects. The magazine Architectural Forum coined the term "194X" to encapsulate this wartime vision of postwar arc